2003
DOI: 10.1046/j.1365-3156.2003.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and diagnostic sensitivity of laboratory tests for Strongyloides stercoralis in travellers compared with immigrants in a non‐endemic country

Abstract: Summaryobjectives To assess whether the clinical and laboratory methods for diagnosing Strongyloides stercoralis infection in non-endemic countries is different between those who are chronically exposed and those who travel.methods Analysis of laboratory and clinical data from 204 patients having S. stercoralis infection at the Hospital for Tropical Diseases, London.results Sixty-four travellers and 128 immigrants from endemic countries had laboratory-proven strongyloides. In those with microscopically proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 29 publications
3
75
0
8
Order By: Relevance
“…We reviewed the titles of all 5189 articles, and evaluated 445 abstracts for potential relevance, eliminating 437 because they did not fulfill our in clusion criteria. Of the remaining eight manuscripts, five pertained to the diagnosis of strongyloidiasis [313][314][315][316] or schistosomiasis, 317 and the remaining three pertained to treatment of these conditions. 318−320 Although our search did not identify any systematic reviews on the diagnosis of either parasite or the treatment of strongyloidiasis, we found a systematic review pertaining to the treatment of schistosomiasis.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the titles of all 5189 articles, and evaluated 445 abstracts for potential relevance, eliminating 437 because they did not fulfill our in clusion criteria. Of the remaining eight manuscripts, five pertained to the diagnosis of strongyloidiasis [313][314][315][316] or schistosomiasis, 317 and the remaining three pertained to treatment of these conditions. 318−320 Although our search did not identify any systematic reviews on the diagnosis of either parasite or the treatment of strongyloidiasis, we found a systematic review pertaining to the treatment of schistosomiasis.…”
Section: Resultsmentioning
confidence: 99%
“…In specific target populations, such as immigrants to non-endemic regions, serology has proven to be a valuable tool for screening and for the evaluation of therapies; 12 however, serology seems to lack sufficient sensitivity to diagnose recently acquired infections. 13 Although serology seems to have good negative predictive value if used in endemic areas, 14 specificity appears to be more problematic as pronounced crossreactivity is observed with other helminths, especially filaria. Specific detection of Strongyloides DNA in human stool samples by real-time PCR has recently been suggested to be a promising alternative diagnostic approach, but needs further exploration.…”
Section: Diagnosis and Global Epidemiology Of Strongyloidesmentioning
confidence: 99%
“…However, patients with chronic Strongyloides infection usually have a low parasite load and irregular shedding making microscopic diagnosis insensitive. Serological methods have higher sensitivity in a chronically infected population [5]. Enzyme-linked immunosorbent assay (ELISA) to detect human immunoglobulin G (IgG) against a crude extract of infective larvae is one of the most widely used techniques for the diagnosis of strongyloidiasis, with sensitivity rates between 73% and 100% [6].…”
mentioning
confidence: 99%